Production of dry toast slices with high nutritional value and attractive color using red beet, spinach, or carrot pastes - Ghada, M. Youssef; Ayat, E. Rizk; Akram, M.M. Elanany; Ahmad, E. Abdel Gawad (Food Technology Research Journal)
Vegetables are essential dietary components, providing a wealth of nutrients, particularly minerals and fiber. This research aimed to enhance dry toast slices' nutritional value and visual appeal by incorporating red beet, spinach, or carrot paste as natural food colorings. A chemical evaluation of the vegetable pastes was conducted, including chemical composition, mineral, phenolic, flavonoid content, and total pigments (betalain, carotene, and chlorophyll). Additionally, antioxidant, antimicrobial, and cytotoxicity activities were measured. The study investigated the effects of adding 30% vegetable paste to the toast dough. The resulting dry toast slices were evaluated for their chemical composition, mineral content, color, physical properties, and sensory characteristics. The results indicated that spinach paste had a higher fat, protein, and ash content than red beet and carrot paste. Furthermore, it exhibited higher amounts of minerals (except P and Cu) than others. The red beet, spinach, and carrot pastes displayed phenolic compound contents of 200, 88, and 18 mg GAE/100g, respectively, while the antioxidant activity values were 90.35, 80.25, and 75.95 %, respectively. The total pigment contents of the pastes were 450 mg/100g betalain for red beet, 120 mg/100g chlorophyll for spinach, and 75 mg/100g carotenoid for carrot. The inhibition zones of the antimicrobial activity for the vegetable pastes, tested against Gram-positive and Gram-negative bacteria, fungi, and yeast, yielded inhibition zones ranging from 8 to 12 mm. The cytotoxic effects of the vegetables on Caco-2 human cancer cell lines followed the order: red beet > spinach > carrot. Fortification of wheat flour with 30% of each vegetable paste resulted in toast with superior sensory characteristics and increased nutritional value compared to the control sample. This research demonstrates the potential of using red beet, spinach, or carrot pastes as natural food colorings to enhance bakery products' nutritional profile and visual appeal.